Apolipoprotein D facilitates rabies virus propagation by interacting with G protein and upregulating cholesterol - Zhang, Hongyan; Liang, Xingxue; Li, Duoduo; Zhang, Chuanliang; Wang, Wenfeng; Tang, Rongze; Zhang, Hongyun; Kiflu, Abraha Bahlbi; Liu, Cheng; Liang, Jingjing; Li, Xiaoning; Luo, Ting Rong (Frontiers in Immunology, 2024)
Rabies virus (RABV) causes a fatal neurological disease, consisting of unsegmented negative-strand RNA, which encodes five structural proteins (3′-N-P-M-G-L-5′). Apolipoprotein D (ApoD), a lipocalin, is upregulated in the nervous system after injury or pathological changes. Few studies have focused on the role of ApoD during virus infection so far. This study demonstrated that ApoD is upregulated in the mouse brain (in vivo) and C8-D1A cells (in vitro) after RABV infection. By upregulating ApoD expression in C8-D1A cells, we found that ApoD facilitated RABV replication. Additionally, Co-immunoprecipitation demonstrated that ApoD interacted with RABV glycoprotein (G protein). The interaction could promote RABV replication by upregulating the cholesterol level. These findings revealed a novel role of ApoD in promoting RABV replication and provided a potential therapeutic target for rabies.